Analysis on the Resource Use Efficiency of Block Farm and Cooperative Schemes in Sugarcane Production - Alcasid, Cleo Jane; Lopez, Harih (Journal of Interdisciplinary Perspectives, 2025)
The primary aim of the study was to determine if there is a significant difference in the resource-use efficiency of sugarcane production between block farm members and cooperative members, using data from 216 farmers in Kiblawan and Hagonoy. A descriptive-comparative research design was utilized from December 2024 to February 2025. Data was analyzed using Frequency Distribution, Mean, Net Profit Margin, Cobb-Douglas production function, Marginal Value Productivity, and Resource Use Efficiency. The majority of respondents were between 52 and 67 years old, male, and almost all were married, having attained tertiary education. They dedicate their entire landholding to sugarcane farming. All the farmers have been in sugarcane production for 5 years or more, while 68.50% are members of the sugarcane farmer cooperative, and all of them have undergone training related to sugarcane production. Farmers who are members of sugarcane cooperatives spend more on labor costs per hectare than their counterparts from block farms. Even with a higher cost of production, cooperative members still reported a slightly higher net income, with a Net Profit Margin of 0.18. Consequently, the benefit-cost ratio is also higher for farmers who are members of the cooperative, at 0.23. All the variables associated with sugarcane production for cooperative member farms are overutilized, and output can be increased by reducing the units of inputs. On the other hand, for farmers under the block farm system, there is a mix of underutilization and overutilization of variables. Labor, land preparation, and transportation costs were underutilized, while the other expenses associated with sugarcane production were overutilized. To increase the efficiency of sugarcane production under block farms, it is necessary to optimize the use of inputs for labor, land preparation, and transportation costs, thereby maximizing productivity while minimizing the overutilization of resources such as machinery and equipment, fertilizers, and pesticides.